2013
DOI: 10.1248/bpb.b12-00792
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of SuHeXiang Wan on Amyloid-β42-Induced Extracellular Signal-Regulated Kinase Hyperactivation and Glial Cell Proliferation in a Transgenic <i>Drosophila</i> Model of Alzheimer’s Disease

Abstract: SuHeXiang Wan (SHXW), a Chinese traditional medicine, has been used to treat infantile convulsions, seizures and strokes. Previously, we reported that modified SHXW, called KSOP1009, suppressed the hyperactivation of c-Jun N-terminal kinase (JNK) and Alzheimer's disease (AD)-like phenotypes in amyloid-β42 (Aβ42)-expressing Drosophila AD models. In the present study, we, further, investigated the detailed mechanism by which KSOP1009 suppresses the AD-like phenotypes of the model flies. As seen in the brains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 46 publications
(57 reference statements)
0
29
0
Order By: Relevance
“…SH-SY5Y Cells were grown at 37°C in an incubator with 5% CO 2 . To investigate the effects of P. multiflorum and S. commixta extracts on cell viability, cells were pre-treated with P. multiflorum or S. commixta extract for 30 min, and then treated with 25 µM Aβ [25][26][27][28][29][30][31][32][33][34][35] (Sigma-Aldrich) for a further 24 h. Then, the cells were incubated with 2 mg/mL of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT; Sigma-Aldrich) at 37°C in a CO 2 incubator for 3 h. MTT medium was carefully aspirated, and the formazan dye was eluted using dimethyl sulfoxide (DMSO). The plate was shaken, and the absorbance was read using a spectrophotometer (Versamax) at a wavelength of 580 nm.…”
Section: Fly Stocks and Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…SH-SY5Y Cells were grown at 37°C in an incubator with 5% CO 2 . To investigate the effects of P. multiflorum and S. commixta extracts on cell viability, cells were pre-treated with P. multiflorum or S. commixta extract for 30 min, and then treated with 25 µM Aβ [25][26][27][28][29][30][31][32][33][34][35] (Sigma-Aldrich) for a further 24 h. Then, the cells were incubated with 2 mg/mL of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT; Sigma-Aldrich) at 37°C in a CO 2 incubator for 3 h. MTT medium was carefully aspirated, and the formazan dye was eluted using dimethyl sulfoxide (DMSO). The plate was shaken, and the absorbance was read using a spectrophotometer (Versamax) at a wavelength of 580 nm.…”
Section: Fly Stocks and Maintenancementioning
confidence: 99%
“…8) Our laboratory study revealed that SuHeXiang Wan, a traditional prescription, is neuroprotective against the cytotoxicity of Aβ42 by using Drosophila AD models. 24,25) In the present study, Drosophila AD models were used to screen 23 medicinal plants from Chinese traditional medicine to identify those that possess protective activity against the Aβ42 neurotoxicity. The study revealed that the extracts of five plants showed neuroprotective activities in Aβ42-expressing flies, as seen by their increased survival rates and recovered eye development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, borneol is a bicyclic monoterpene present in several medicinal plants (91)(92)(93)(94). Previous studies showed that borneol has free radical scavenging activity (95) and is a major component of essential oil of SuHeXiang Wan (92) whose neuroprotective function has been reported in in vivo and in vitro models of Alzheimer's disease (AD) (96)(97)(98)(99). Moreover, a recent study showed that borneol exerts a neuroprotective effect against β-amyloid (Aβ) cytotoxicity via upregulation of nuclear translocation of Nrf2 and expression of Bcl-2 (100).…”
Section: Terpenes and Neuronal Healthmentioning
confidence: 99%
“…Therefore, inhibitors of these signaling molecules are potentially therapeutic drugs. Indeed, when Drosophila AD models were treated with inhibitors of JNK or ERK, their AD-like phenotypes were alleviated [70, 101]. …”
Section: Drosophila As a Model System For Neurodegenerative Diseasesmentioning
confidence: 99%